Evaluation of the Final Senior Secondary School Visual Art Project/Practical Works: A Case Study of Some Schools in Ashanti Region - Antwi-Boadi, Emmanuel (2013)
A Thesis submitted to the Board of Post-Graduate Studies in partial fulfillment of the requirements for the MASTER OF ARTS Degree in Art Education,2012